The Turkana Food Environment - Induli, Mudiovo Irene; Nowicki, Marisa (2022)
Data was collected at 3 levels: the households using in-depth interviews, market vendors by geocoding, mapping, stock inventorying and verbal interviews; and policy makers using key informant interviews. The purpose of the study was to assess Turkana’s food environment and evaluate its influence on diet quality by: • Assessing the distribution of food vendors, and their vendor type, in Turkana County • Assessing household food environments, including food sources • Evaluating the availability, affordability, convenience, safety/quality, promotion, and sustainability of food items within Turkana County • Assessing the safety and quality of food in Turkana County from a vendor and consumer perspective • Assessing the county and national government policies and programs shaping the food environment The study sought to answer the following questions: • Does the food environment promote healthy diets? • What are the main sources of food at the household level? • Which factors influence the foods sold in the market? • Which foods and beverages are most readily available on the (informal or formal) market? • Which factors influence food affordability? • What factors are influencing food quality and safety? • What is the cost of a healthy diet in Turkana County? • What government initiatives and policies are influencing the food environment? The food environment was assessed following the key elements of availability, affordability, convenience, promotion, quality, and sustainability of foods and beverages in wild, cultivated, and built spaces that are influenced by the socio-cultural and political environment and ecosystems within which they are embedded. The datasets are: 1. Household data- transcribed scripts 2. Market vendor data- geocoded and mapped vendors and coded interview responses 3. Policy makers’ data- coded key informant interviews